1971
DOI: 10.1097/00006842-197111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Personality and Treatment Conditions Associated with Success in a Smoking Control Program

Abstract: A total of 104 men who were heavy smokers (minimum of a pack, and averaging 35 cigarettes a day) participated in a 10-week program to break the habit. The majority (N=83) received group therapy, and the remainder were seen individually. Each S was randomly assigned to one of the following drug conditions: no pills, placebo, lobeline, dextroamphetamine and imipramine. Pretesting established each S as a good (N=67) or poor (N=37) risk to stop smoking. Results indicated that, both at the end of treatment and at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…This is reminiscent of findings over short periods of time in clinic studies by Schwartz and Dubitzky," Thompson and Wilson,43 and Jacobs, et al 44 We also found this to be the case for spontaneous smoking withdrawal in our random sample of Buffalo.7…”
Section: Support Of Spousesupporting
confidence: 83%
“…This is reminiscent of findings over short periods of time in clinic studies by Schwartz and Dubitzky," Thompson and Wilson,43 and Jacobs, et al 44 We also found this to be the case for spontaneous smoking withdrawal in our random sample of Buffalo.7…”
Section: Support Of Spousesupporting
confidence: 83%
“…These follow-up points have included immediately post-treatment [as in a study by Keutzer (37)], two weeks post-treatment (39), three-month follow-up (40), six-week follow-up (41), one-year follow-up (42), and three to four-year follow-ups (38,16).…”
Section: Follow-up Diff Erences and Deficienciesmentioning
confidence: 99%
“…There are no long term studies of doxepin and imipramine, but short term trials suggest that imipramine does not significantly reduce cigarette consumption compared to a no-medication control [337]. Although doxepin improves cravings, two months sustained abstinence rates are similar to placebo [338].…”
Section: Relative Efficacymentioning
confidence: 99%